Budget Deficit: A Dilemma of Pakistan’s Economy - Faridi , Muhammad Zahir; Ahmad, Rashid; Hussain, Altaf; Usama, Ahmad (iRASD Journal of Economics, 2022)
The study has been carried out for investigating the effects of nominated independent variables on the budget deficit of Pakistan. For it, data has been collected for the period ranging from 1972 to 2019. ARDL Technique has been employed for carrying out the empirical analysis. The dependent variable is budget deficit; however, oil price hikes, work remittances, per capita income, corruption, and GDP deflator is marked as the independent variable. The fallouts of the empirical analysis reveal that there exists a direct association among the dependent and independent variables except for per capita income and work remittances as they are related indirectly.